Enhancing Services to Develop an Effective Loyalty Program for IKANO Financial Services - Shah, Rushabh (2011)
The purpose of this project is to investigate loyalty market in the UK, to give IKANO Financial Services an understanding of their current position compared to competitors and to enhance IKANO‟s loyalty program services to gain a competitive edge in the market.